TRIPARTITE PARTNERSHIP PATTERNS IN INCREASING THE BIRTH RATE BY HEALTH WORKERS IN CIGINGGANG VILLAGE - Mimin Megawati; Nanik Yuliwati (International Journal of Medicine and Health, 2023)
Health is a basic right of all people. The main priority at this time is health services for pregnant women. The selection of birth attendants for pregnant women is something that must be considered. Prior to the tripartite partnership, many people chose to give birth with the help of a dukun than to give birth with a health worker. The process of forming a tripartite partnership, namely collaboration between cadres, traditional birth attendants and midwives, began with the signing of the MoU which was directly supervised by the camat, babinsa and lurah. The existence of cadres and traditional birth attendants who continuously accompany pregnant women makes them trust them to use the services of health workers and give birth at health facilities. There was an increase in the number of birth mothers assisted by midwives who partnered with traditional birth attendants at Poskesdes with an average increase of 2. 8% for the past 2 years. The obstacles in implementing this tripartite partnership are the very low level of education of cadres and traditional birth attendants, the remote location of health services and the financial capacity of postpartum mothers.